Z-Essential Submodules - Abbas , Muntaha khudhair; Talebi , Yahya; Hadi , Inaam M. Ali (Iraqi Journal of Science, 2024)
We define and investigate Z- essential submodules as a generalization of essential submodules. Various characterizations and properties of Z-essential submodules are given. Moreover we introduce the concepts of Z-singular submodule and Z-closed submodules.